Long-Term Cognitive and Psychological Functioning in Post–Electroconvulsive Therapy Patients. Issue 1 (March 2019) - Miller, Michelle L.; Luu, Hien; Gaasedelen, Owen; Hahn-Ketter, Amanda E.; Elmore, Alexis; Dezhkam, Naseem; Bayless, John; Moser, David J.; Whiteside, Douglas M.
Abstract : Objective: Electroconvulsive therapy (ECT) is associated with positive outcomes for treatment-resistant mood disorders in the short term. However, there is limited research on long-term cognitive or psychological changes beyond 1 year after -ECT. This study evaluated long-term outcomes in cognitive functioning, psychiatric symptoms, and quality of life for individuals who had undergone ECT. Methods: Eligible participants (N = 294) who completed a brief pre-ECT neuropsychological assessment within the last 14 years were recruited for a follow-up evaluation; a limited sample agreed to follow-up testing (n = 34). At follow-up, participants were administered cognitive measures (Repeatable Battery for the Assessment of Neuropsychological Status [RBANS], Wide Range Achievement Test-4 Word Reading, Trail Making Test, Wechsler Adult Intelligence Scale—Fourth Edition Letter Number Sequence and Digit Span, and Controlled Oral Word Association Test), along with emotional functioning measures (Beck Depression Inventory—Second Edition [BDI-II] and Beck Anxiety Inventory) and the World Health Organization Quality of Life–BREF quality of life measure. Follow-up-testing occurred on average (SD) 6.01 (3.5) years after last ECT treatment. Results: At follow-up, a paired t test showed a large and robust reduction in mean BDI-II score. Scores in cognitive domains remained largely unchanged. A trend was observed for a mean reduction in RBANS visual spatial scores. Lower BDI-II scores were significantly associated with higher RBANS scores and improved quality of life. Conclusions: For some ECT patients, memory, cognitive functioning, and decreases in depressive symptoms can remain intact and stable even several years after ECT. However, the selective sampling at follow-up makes these results difficult to generalize to all post-ECT patients. Future research should examine what variables may predict stable cognitive functioning and a decline in psychiatric symptoms after ECT.